Excitability of sensory axons in amyotrophic lateral sclerosis. Issue 7 (July 2018) - Matamala, José Manuel; Howells, James; Dharmadasa, Thanuja; Huynh, William; Park, Susanna B.; Burke, David; Kiernan, Matthew C.
Highlights: Excitability properties of sensory axons were investigated in ALS patients. Axonal membrane properties were normal in sensory nerves of ALS. Sensory dysfunction may result from a ganglionopathy or more proximal central abnormalities. Abstract: Objective: To evaluate the excitability of sensory axons in patients with amyotrophic lateral sclerosis (ALS). Methods: Comprehensive sensory nerve excitability studies were prospectively performed on 28 sporadic ALS patients, compared to age-matched controls. Sensory nerve action potentials were recorded from digit 2 following median nerve stimulation at the wrist. Disease severity was measured using motor unit number estimation (MUNE), the revised ALS Functional Rating Scale (ALSFRS-R) and the MRC scale. Results: There were no significant differences in standard and extended measures of nerve excitability between ALS patients and controls. These unchanged excitability measures included accommodation to long-lasting hyperpolarization and the threshold changes after two supramaximal stimuli during the recovery cycle. Excitability parameters did not correlate with MUNE, ALSFRS-R, APB MRC scale or disease duration. Conclusions: This cross-sectional study has identified normal axonal membrane properties in myelinated sensory axons of ALS patients. Previously described sensory abnormalities could be the result of axonal fallout, possibly due to a ganglionopathy, or to involvement of central sensory pathways rostral to gracile and cuneate nuclei. Significance: These results demonstrate the absence of generalized dysfunction of the membrane properties of sensory axons in ALS in the face of substantial deficits in motor function.